BACKGROUND EZETIMIBE USE AMONG PARTICIPANTS IN THE CLEAR OUTCOMES TRIAL - Luke J. Laffin; Danielle Brennan; LeAnne Bloedon; Na Li; Steven E. Nissen (Elsevier, 2023)
Therapeutic Area: ASCVD/CVD Risk Reduction Background: The Cholesterol Lowering via Bempedoic acid, an ACL-Inhibiting Regimen (CLEAR) Outcomes trial randomized statin-intolerant patients with, or at high risk for, atherosclerotic cardiovascular disease (ASCVD) to bempedoic acid or placebo and assessed its impact on major adverse cardiovascular events (MACE). CLEAR Outcomes demonstrated a reduction in the primary 4-component MACE endpoint of death from cardiovascular causes, nonfatal myocardial infarction, nonfatal stroke, or coronary revascularization. Although patients attested to their inability to take a statin, they could be taking non-statin background lipid lowering therapy including ezetimibe. Ezetimibe is an inhibitor of intestinal cholesterol absorption whose use is recommended in contemporary cholesterol guidelines because it has been shown to decrease low density lipoprotein cholesterol (LDL-C) and, when taken in combination with statins, decrease MACE. A combination of ezetimibe and bempedoic acid is FDA approved for lowering of LDL-C and investigators sought to determine the impact of bempedoic acid compared with placebo among patients taking ezetimibe at trial commencement. Methods: Among participants taking ezetimibe, the impact of bempedoic acid on LDL-C, high sensitivity C-reactive protein (hsCRP), and MACE was assessed. Results: CLEAR Outcomes included 13,970 participants of which 11.5% were taking ezetimibe at the time of randomization. These participant characteristics are seen in Table 1. At 6 months participants randomized to bempedoic acid demonstrated a -28.1 % change in LDL-C (95%CI,-30.2 to -25.9,p<0.0001) and -30.5% change in hsCRP (95%CI,-36.2 to -24.8,p<0.0001) compared with placebo. Safety was similar among both groups and compared similarly to overall study findings with a higher incidence of gout (4.5% vs 2.1% in the placebo arm) and cholelithiasis (1.4% vs 0.5%.) Numerically less 4-component MACE occurred among participants randomized to bempedoic acid, however this difference was not statistically significant (127 [15.8%] vs. 134 [16.6%]; HR, 0.94; 95%CI, 0.74 to 1.20; p=0.89). Three-component MACE (death from cardiovascular causes, nonfatal myocardial infarction, nonfatal stroke) was also numerically less (74 [9.2%] vs. 86 [10.6%]; HR, 0.85; 95%CI, 0.62 to 1.16; p=0.69). Conclusions: Bempedoic acid use among individuals taking ezetimibe at the beginning of the CLEAR Outcomes trial was well tolerated with efficacy and safety similar to the overall trial population.